Pengaruh segmentasi pasar terhadap kepuasan pelanggan (nasabah) pada Bank BPR Jatim Cabang Ponorogo - Elis Tri Wahyuni (EQUILIBRIUM: Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
This study aims to determine the effect of market segmentation of customer satisfaction (Customer) in bank BPR Jatim Branch of Ponorogo. Market Segmentation effect on customer satisfaction as evidenced from t value on the market cementation variable (X) is from a significant level of 0.000 t less than 0.05 then the research hypothesis H0 and menerimaHa resisting. And it can be seen the value rhitung is 0.748 while rtabel 0,138. This